2018
DOI: 10.1016/j.humpath.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of EZH1 mutations in the diagnosis of follicular-patterned thyroid tumors

Abstract: Follicular-patterned tumors of the thyroid gland are characterized by a predominantly follicular growth pattern. They frequently harbor RAS mutations, not BRAF mutations. Technological advances in molecular testing have discovered novel RAS-type mutations. However, clinical significance of these mutations remains unknown. We investigated the prevalence and clinical impact of mutations of BRAF, NRAS, HRAS, KRAS, EZH1, EIF1AX, and TERT genes by Sanger sequencing in a series of 201 follicular-patterned thyroid tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Hyperfunctioning FA has mutations in TSHR , GNAS and EZH1 genes . EZH1 mutations also occur in Hürthle cell adenoma and minimally invasive FTC . RAS mutations are frequent in NIFTP, as well as PAX8/PPARG and THADA//IGF2BP3 fusions .…”
Section: Genetic Profiles and Molecular Diagnosis Of Thyroid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperfunctioning FA has mutations in TSHR , GNAS and EZH1 genes . EZH1 mutations also occur in Hürthle cell adenoma and minimally invasive FTC . RAS mutations are frequent in NIFTP, as well as PAX8/PPARG and THADA//IGF2BP3 fusions .…”
Section: Genetic Profiles and Molecular Diagnosis Of Thyroid Tumorsmentioning
confidence: 99%
“…203 EZH1 mutations also occur in H€ urthle cell adenoma and minimally invasive FTC. 204 RAS mutations are frequent in NIFTP, as well as PAX8/PPARG and THADA//IGF2BP3 fusions. 1,200 BRAF K601E and small insertions or deletions surrounding codon 600 of BRAF can occur, 93,200 but NIFTP should not have BRAF V600E , TERT or TP53 mutations, or RET/ PTC fusions, which have a risk of malignancy of nearly 100%.…”
Section: Genetic Profiles and Molecular Diagnosis Of Thyroid Tumorsmentioning
confidence: 99%
“…To validate the specificity of the VE1 antibody, we performed the VE1 IHC in 71 RAS-mutant non-PTC tumors including follicular neoplasms, Hürthle cell neoplasms, and poorly differentiated carcinomas that were employed in our previous study [53].…”
Section: Ve1 Immunohistochemistrymentioning
confidence: 99%
“…Molecular tests are helpful but not required for NIFTP diagnosis. BRAFV600E, RET/PTC fusions or gene mutations such as TERT promoter or TP53 exclude a diagnosis of NIFTP (Nikiforov et al 2018), but it has been observed that if the morphological diagnostic criteria are strictly observed, these mutations are very unlikely to occur (Nikiforov et al 2016;Johnson and Sadow 2018;Jung et al 2018;Kim et al 2018a), apart from some exceptional cases (Kim et al 2018b).…”
Section: Histology Of Niftpmentioning
confidence: 99%